2014
DOI: 10.1038/ijo.2014.126
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic fat storage in the pancreas using 1H-MRS: importance of diabetic status and modulation with bariatric surgery-induced weight loss

Abstract: Pancreatic fat increased with T2D and drastically decreased after the bariatric surgery. This suggests that decreased PTGC may contribute to improved beta cell function seen after the bariatric surgery. Further, long-term interventional studies are warranted to examine this hypothesis and to determine the degree to which ectopic fat mobilization may mediate the improvement in endocrine and exocrine pancreatic functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 47 publications
6
72
1
5
Order By: Relevance
“…Bariatric surgery has become the standard treatment for morbidly obese patients. It can decrease the size of PPF 40 . Long-term follow-up after bariatric surgery has confirmed significant weight loss as well as a decrease in the occurrence of multiple cancer types, in particular, breast and endometrial cancer 4143 .…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery has become the standard treatment for morbidly obese patients. It can decrease the size of PPF 40 . Long-term follow-up after bariatric surgery has confirmed significant weight loss as well as a decrease in the occurrence of multiple cancer types, in particular, breast and endometrial cancer 4143 .…”
Section: Discussionmentioning
confidence: 99%
“…Actually, important information must be taken in account: (1) some studies have found no correlation between NAFLD and NAFPD[80,156]; (2) hepatic fat is mainly intracellular, while NAFPD is a consequence of adipocytes infiltration[5,16]; (3) when patients are treated with bariatric surgery, fat loss in the liver and the pancreas seem to be independent, suggesting tissue-specific mobilization of these ectopic fat stores[77]; and (4) when corrected for BMI, the association between hepatic and pancreatic steatosis can’t be found anymore[33,134,137]. …”
Section: Pathogenesis and Risk Factorsmentioning
confidence: 99%
“…Values of greater than 20% have been reported [8, 9, 11], well in excess of histological estimation [24, 27]. Quantification of the percentage of fat within the parenchyma of the pancreas is challenging as it depends upon delineating tissue entirely within the organ.…”
Section: Introductionmentioning
confidence: 99%